Особливості морфології та текстури кремнеземних і вуглецевих адсорбентів - Гунько, В. М. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
The morphological and textural characteristics of various silicas (93 fumed silicas and 56 porous silicas), different carbons (230), and porous polymers (53) are analyzed using probe (nitrogen, argon, benzene, n-decane, water) adsorption, small angle X-ray scattering (SAXS), and transition (TEM), scanning (SEM) electron and atom force (AFM) microscopies. There are certain correlations between pore volume (Vp) and specific surface area (SSA, SBET) for these materials. Synthesis and treatment temperatures affect this relationship since a linear Vp - SBET approximation scatter decreases with decreasing these temperatures. Silicas are composed of nonporous nanoparticles (NPNP), but activated carbons (AC) are composed of porous nanoparticles (PNP). For different materials, NP are weakly or strongly packed in secondary structures. However, there are general features of pore size distributions (PSD) for NP-based materials, e.g., minimal contribution of narrow mesopores of 3-5 nm in radius due NP-packing effects. For AC produced using the same chars and activation agents but with varied activation time, the textural characteristics demonstrate smooth changes with increasing burn-off degree: nanopores partially transform into narrow mesopores with opposite PSD shifts of broad mesopores and macropores. Comparison of adsorption (open pores accessible for probes) and SAXS (both open and closed pores) data for carbons shows that the difference decreases with increasing burn-off degree due to decreasing contribution of closed pores. Most clear pictures on the particulate morphology and texture could be obtained in parallel analysis using adsorption, SAXS, and microscopic methods with appropriate data treatments.